Geography, Ethnicity or Subsistence-Specific Variations in Human Microbiome Composition and Diversity - Gupta, Vinod K.; Paul, Sandip; Dutta, Chitra (Frontiers in Microbiology, 2017)
One of the fundamental issues in the microbiome research is characterization of the healthy human microbiota. Recent studies have elucidated substantial divergences in the microbiome structure between healthy individuals from different race and ethnicity. This review provides a comprehensive account of such geography, ethnicity or life-style-specific variations in healthy microbiome at five major body habitats – Gut, Oral-cavity, Respiratory Tract, Skin and Urogenital Tract (UGT). The review focuses on the general trend in the human microbiome evolution - a gradual transition in the gross compositional structure along with a continual decrease in diversity of the microbiome, especially of the gut microbiome, as the human populations passed through three stages of subsistence like foraging, rural farming and industrialized urban western life. In general, gut microbiome of the hunter-gatherer populations is highly abundant with Prevotella, Proteobacteria, Spirochaetes, Clostridiales, Ruminobacter etc., while those of the urban communities are often enriched in Bacteroides, Bifidobacterium and Firmicutes. The oral and skin microbiome are the next most diverse among different populations, while respiratory tract and UGT microbiome show lesser variations. Higher microbiome diversity is observed for oral-cavity in hunter-gatherer group with higher prevalence of Haemophilus than agricultural group. In case of skin microbiome, rural and urban Chinese populations show variation in abundance of Trabulsiella and Propionibacterium. On the basis of published data, we have characterized the core microbiota – the set of genera commonly found in all populations, irrespective of their geographic locations, ethnicity or mode of subsistence. We have also identified the major factors responsible for geography-based alterations in microbiota; though it is not yet clear which factor plays a dominant role in shaping the microbiome – nature or nurture, host genetics or his environment. Some of the geographical/racial variations in microbiome structure have been attributed to differences in host genetics and innate/adaptive immunity, while in many other cases, cultural/behavioral features like diet, hygiene, parasitic load, environmental exposure etc. overshadow genetics. The ethnicity or population-specific variations in human microbiome composition, as reviewed in this report, question the universality of the microbiome-based therapeutic strategies and recommend for geographically tailored community-scale approaches to microbiome engineering.